Cox4i2 Triggers an Increase in Reactive Oxygen Species, Leading to Ferroptosis and Apoptosis in HHV7 Infected Schwann Cells - Chang, Bowen; Guan, Haochen; Wang, Xueyi; Chen, Zheng; Zhu, Wanchun; Wei, Xiangyu; Li, Shiting (Frontiers in Molecular Biosciences, 2021)
Emerging evidence suggests that reactive oxygen species (ROSs) play a significant role in the pathogenesis of peripheral nerve damage. Our previous study indicated that human herpesvirus 7 (HHV7) induces Bell’s palsy. However, the specific mechanism underlying the effects of ROSs in HHV7 infection-induced facial nerve damage is unknown. In this study, we established a rat FN model by inoculating an HHV7 virus solution. The facial grading score and LuxolFastBlue (LFB) staining were used to assess the success of the model. Using mRNA-sequencing analysis, we found that the expression of Complex IV Subunit 4 Isoform 2 (Cox4i2) increased in infected Schwann cells (SCs). Cox4i2 was suggested to increase COX activity, thereby promoting ROS production. The changes in the endogenous oxidant and antioxidant system were assessed, and the results showed that oxidative stress increased after HHV7 infection in vivo and in vitro. However, we found that oxidative injury was relieved after the transfection of shCox4i2 in HHV7-treated SCs by evaluating cell death, cell proliferation, and the ROS level as well as the levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH). Furthermore, we hypothesised that Cox4i2 loss would attenuate HHV7-induced ferroptosis and apoptosis, which are closely related to ROSs in SCs. Our research illustrated that the knockdown of Cox4i2 suppresses HHV7-induced RSC96 cell ferroptosis as well as apoptosis via the ERK signalling pathway. Overall, several in vitro and in vivo methods were adopted in this study to reveal the new mechanism of ROS-induced and Cox4i2-mediated apoptosis and ferroptosis in HHV7 infected SCs.